Development of Various Leishmania (Sauroleishmania) tarentolae Strains in Three Phlebotomus Species - Ticha, Lucie; Kykalova, Barbora; Sadlova, Jovana; Gramiccia, Marina; Gradoni, Luigi; Volf, Petr (Microorganisms, 2021)
Leishmania (Sauroleishmania) tarentolae is transmitted by reptile-biting sand flies of the genus Sergentomyia, but the role of Phlebotomus sand flies in circulation of this parasite is unknown. Here, we compared the development of L. (S.) tarentolae strains in three Phlebotomus species: P. papatasi, P. sergenti, and P. perniciosus. Laboratory-bred sand flies were membrane-fed on blood with parasite suspension and dissected on days 1 and 7 post blood meal. Parasites were measured on Giemsa-stained gut smears and five morphological forms were distinguished. In all parasite-vector combinations, promastigotes were found in Malpighian tubules, often in high numbers, which suggests that this tissue is a typical location for L. (S.) tarentolae development in sand flies. All three studied strains colonized the hindgut, but also migrated anteriorly to both parts of the midgut and colonized the stomodeal valve. Significant differences were demonstrated between sand fly species: highest infection rates, high parasite loads, and the most frequent anterior migration with colonization of the stomodeal valve were found in P. perniciosus, while all these parameters were lowest in P. sergenti. In conclusion, the peripylarian type of development was demonstrated for three L. (S.) tarentolae strains in three Phlebotomus sand flies. We suggest paying more attention to Phlebotomus species, particularly P. perniciosus and P. papatasi, as potential secondary vectors of Sauroleishmania.
Keywords: sand flies; Sauroleishmania; Leishmania tarentolae; experimental infections; Phlebotomus